THE EFFECTIVENESS OF AN ACTIVITY-BASED APPROACH TO TEACHING THE PAST TENSE IN MEDICAL ENGLISH FOR PROFESSIONAL PURPOSES - Yu.V. Lysanets; O.M. Bieliaieva; I.V. Znamenska; H.Yu. Morokhovets; I.V. Rozhenko (Проблеми екології та медицини)
The present paper explores the methods for effective mastering the past tense relying on an activity-based approach following the Common European Framework of Reference for Languages. The aim of the research is to facilitate the teaching and revising the grammar material on the past simple (indefinite) tense, the past continuous (progressive) tense, and the past perfect tense in the process of training undergraduates, Ph.D. students, academic and clinical teachers at a medical university. The results of the research have been integrated into the 1st edition of “Medical English for Academic Purposes” (2018) and “Medical English for Public Health Purposes” (2021). The authors developed the methodological mechanisms to support courses in professional English at higher medical educational institutions through an activity-based approach, which ensures the effective acquisition of a foreign language, promotes the formation of a linguistic personality capable not only of communicating in all areas, but also of successful integration into the international community. The paper provides a wide range of scaffolding activities and methods: using visuals (graphic organizers, charts, etc.), selecting historically meaningful texts, peer-to-peer talk, strategic pairings, “real-life tasks” and modelling situations, the “fishbowl” model and others. The suggested methodological algorithm is feasible for both oral and written communication, reading and listening comprehension activities, group work, individual and self-directed work in class, as well as for in-class or self-paced learning, depending on the features of the curriculum and students’ English proficiency. The receptive aspect of teaching is represented by read-and-translate exercises, targeted texts describing significant events in the history of medicine, as well as true-false exercises to check students’ comprehension. Meanwhile, the reproductive aspect of teaching covers exercises involving opening the brackets, filling the blanks, as well as creating negative and interrogative forms of verbs. Eventually, the productive aspect of teaching is ensured by a wide range of creative speaking and writing activities and “real-life tasks”, aimed at developing students’ communicative competence in English for Professional Purposes (in-class speaking activities (peer-to-peer talk, class discussion). In addition, collecting family history is yet another pragmatically feasible task to revise and study past tenses. The application of an activity-based approach to teaching the past tenses at a medical university is highly effective to foster essential job-related skills, experience and professional readiness. The authors believe that this, in turn, will promote academic mobility and scientific cooperation, thus contributing to the development of higher medical education in Ukraine, which renders the research relevant.